Study of active compounds in Zingiberaceae and Niacin content in Broken Rice for herbal soap formulation - Wongpriaw, Napatsorn; Thammasom, Thitinan; Puttanu, Bussabavadee; Tanmuangpak, Kitti; Sudwilai, Wilailux (Creative Science, 2025)
This research studied the chemical composition of three species from the Zingiberaceae family (Curcuma longa L., Curcuma aromatica Salisb. and Zingiber montanum (J.Koening) Link ex A.Dietr.) and analyzed the niacin content in extracts from four cultivars of broken rice, namely Daeng Mueang Loei, Siw Kliang Mueang Loei, Black Sticky Rice and Sticky Rice RD6, for use as active ingredients in the development of herbal soap formulations, as an option to add value to the rice farming community of Ban Nam Yen, Dan Sai District, Loei Province. The study of active compounds Zingiberaceae using HS-GCMS revealed that C. longa L. and Z. montanum (J.Koening) Link ex A.Dietr.) contained Bicyclo[3.1.0] hexane, 4-methylene-1-(1-methylethyl)- (cis-sabinene) as the highest component, while C. aromatica Salisb. had (R)-1-Methyl-4-(6-methylhept-5-en-2-yl)cyclohexa-1,4-diene (beta-Curcumene) as the predominant compound. Quantitative analysis of curcumin by UV-Visible spectrophotometry showed that C. longa had the highest curcumin content at 2.92± 0.13 g 100g-1. For the analysis of niacin content in broken rice by HPLC, Daeng Mueang Loei was found to have the highest content at 5.69±0.19 mg kg-1, whereas niacin was not detected in Black Sticky Rice. Method validation confirmed reliability for the quantitative analysis (R² ≥ 0.9950, %RSD ≤11%, 80-110% recovery). Formula 1 demonstrated superior physical and chemical properties in the base formula, identifying it as suitable for herbal soap development. These results establish foundational data for developing products incorporating rice and Zingiberaceae extracts. GRAPHICAL ABSTRACT HIGHLIGHTS Active Compounds in Zingiberaceae: The study using HS-GCMS identified that longa and Z. montanum contained cis-sabinene as the highest component, while C. aromatica had β-Curcumene as the predominant compound. Curcumin content in longa: The quantitative analysis of curcumin by UV-visible spectroscopy revealed that C. longa contained the highest curcumin content at 2.9173±0.13 g/100g. Niacin content in broken rice: The HPLC analysis showed that Daeng Mueang Loei had the highest niacin content at 5.6943±0.19 mg/kg, while niacin was not detected in Black Sticky Rice. Method validation: The method validation confirmed the reliability of the quantitative analysis, with R² ≥ 0.9950, %RSD < 11%, and a recovery rate between 80-110%. Herbal soap development: Formula 1 exhibited superior physicochemical properties compared to the base formula, indicating its suitability for herbal soap development. Foundational data: The results provide basic data for the development of products incorporating rice and Zingiberaceae plant extracts.